Postictal Psychosis: Case Report and Literature Review - Joana Regala; João Lourenço; Francisco Moniz-Pereira; António Bento (Case Reports in Psychiatry)
Postictal psychosis (PIP) is one of the most common types of psychosis in epileptic patients. By virtue of the paucity of research on PIP, its pathophysiology remains not completely understood. Our case report describes a clinical picture of PIP, characterized by pleomorphic features, with neither Schneider’s first-rank symptoms nor negative symptoms of schizophrenia, in a longstanding epileptic female patient with a history of nonadherence to antiepileptic treatment and poorly controlled seizures. Additionally, she had previous cognitive impairment and encephalomalacia in the right parietooccipital region as a sequela of a moderate-to-severe traumatic brain injury known to precede the emergence of the epilepsy. In light of our findings, we critically reviewed the current literature on postictal psychoses providing insight into its neurobiological underpinnings.